Evaluasi Instalasi Pengolahan Air Limbah pada Salah Satu Rumah Sakit di Wilayah Kota Surabaya - Anggoro, Cahyo; Mirwan, Mohamad (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Hospital wastewater has different characteristics from industrial wastewater and other wastewater. This hospital utilizes a wastewater treatment plant (WWTP) that operates through chemical, physical, and biological processes. This study aimed to evaluate the performance of the WWTP installed at a hospital in Surabaya. The study used both quantitative and qualitative approaches to analyze the hospital’s treatment system. The evaluation included data on clean water usage and waste effluent, as well as data on wastewater parameters. The WWTP units installed at this hospital include a chemical processing tank, grease trap, aerobic biofilter tank, anaerobic biofilter tank, sedimentation tank, and sump pit. Laboratory testing data over the past few months indicates that the WWTP is not performing optimally.